PPy / NiCo-LDH / NF composite material and preparation method and application thereof

The existing nickel-cobalt layered bimetallic hydroxide and polypyrrole were combined on a foam nickel substrate and the preparation of PPy/NiCo-LDH/NF composite material was solved by combining NiCo layered bimetallic hydroxide and polypyrrole on a foamed nickel-cobalt substrate using ZIF template guidance strategy and electrochemical polymerization method. The problems of low conductivity, unstable structure and insufficient electrocatalytic performance of the double hydroxide electrode material have achieved excellent HER and OER electrocatalytic activity at the same time in alkaline media and maintained good cycling stability.

CN119425806APending Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202411464897.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing nickel-cobalt layered double hydroxide electrode materials have problems such as low conductivity, unstable structure, inability to show excellent OER and HER performance at the same time, complex preparation process and high cost.

Method used

PPy/NiCo is prepared by combining NiCo layered bimetallic hydroxide and polypyrrole on a foam nickel substrate, and polypyrrole is compounded on the surface of NiCo layered bimetallic hydroxide, and PPy/NiCo is prepared by ZIF template guidance strategy and electrochemical polymerization method. -LDH/NF composite material.

Benefits of technology

It realizes that both excellent HER and OER electrocatalytic activities are exhibited in alkaline media, and maintains good cycle stability after 1000 cycles, reducing preparation costs and simplifying the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425806A_ABST
    Figure CN119425806A_ABST
Patent Text Reader

Abstract

The invention discloses a PPy / NiCo-LDH / NF composite material and a preparation method and application thereof, and belongs to the technical field of electrocatalyst preparation. The PPy / NiCo-LDH / NF composite material provided by the invention comprises a foamed nickel substrate as well as NiCo layered double hydroxides and polypyrrole which are compounded on the foamed nickel substrate, the polypyrrole is compounded on the surface of the NiCo layered double-metal hydroxide. The surface of NiCo layered double hydroxides is induced and modified by polypyrrole, so that the layered double hydroxides are arranged more regularly and densely, efficient mass transfer of electrons is facilitated, an electron transfer interface can be induced, the composite material exposes more catalytic active sites, the electron interaction is enhanced, and the catalytic activity of the composite material is improved. According to the present invention, with the preparation method, the excellent electrocatalytic activity is provided for the HER and the OER in the alkaline medium, and the excellent cycle stability is provided for the HER and the OER in the alkaline medium after the 1000 times of cycle, such that the wide application prospect in the electrocatalytic reaction is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrocatalyst preparation, and in particular, relates to a PPy / NiCo-LDH / NF composite material and a preparation method and application thereof. Background Art

[0002] Nickel cobalt layered double hydroxide (NiCo-LDH) has a very high theoretical capacity due to its reasonable mesopore size distribution, high specific surface area, multivalent states of nickel and cobalt elements, and the synergistic effect of the two elements. It has attracted widespread attention because of its abundant raw materials, low cost, and non-toxicity. However, its low conductivity and structural instability shorten the cycle life of the electrode. Conductive polymers (polypyrrole, polyaniline, polythiophene, etc.) are usually introduced to improve the electrochemical properties of composite materials. However, the composite materials made by the existing preparation process are easy to agglomerate and difficult to control, resulting in poor conductivity and poor structural stability of the material, which cannot meet the actual use requirements. Therefore, it is necessary to improve the existing nickel cobalt layered double hydroxide electrode materials to improve their comprehensive performance.

[0003] The prior art with application publication number CN 116825548A discloses a nickel-cobalt layered hydroxide-coated polypyrrole tube composite material, in which the nickel-cobalt layered hydroxide is coated on the polypyrrole nanotube by a hydrothermal method using an imidazolate framework as a template to prepare a composite material with excellent electrochemical properties.

[0004] However, existing composite materials have the following problems: first, nickel-cobalt layered double hydroxide materials are easy to fold and agglomerate, which leads to low conductivity and unstable structure; second, they do not have excellent OER and HER performance in the same electrolyte; third, the preparation process is complicated and costly, which is not conducive to industrial production. Summary of the invention

[0005] The present application discloses a PPy / NiCo-LDH / NF composite material and its preparation method and application, aiming to solve the technical problems of existing composite materials such as low conductivity, unstable structure, inability to simultaneously exhibit excellent OER and HER performance, complex preparation process and high cost.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a PPy / NiCo-LDH / NF composite material, the composite material comprising a nickel foam substrate and a NiCo layered double metal hydroxide and polypyrrole composited on the nickel foam substrate;

[0008] The polypyrrole is compounded on the surface of the NiCo layered double metal hydroxide.

[0009] In combination with the first aspect, preferably, the composite material has a nanosheet array structure.

[0010] The second aspect of the present application provides a method for preparing the PPy / NiCo-LDH / NF composite material according to the first aspect, the method comprising:

[0011] The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor;

[0012] The L-Co-ZIF / NF precursor is dissolved in an aqueous solution of Ni(NO3)2·6H2O, reacted at room temperature, separated and collected to obtain NiCo-LDH / NF;

[0013] The pyrrole is electrodeposited and polymerized onto the surface of the NiCo-LDH / NF to obtain a PPy / NiCo-LDH / NF composite material.

[0014] In combination with the second aspect, preferably, the mass ratio of Co(NO3)2·6H2O, 2-methylimidazole and Ni(NO3)2·6H2O is 0.6-0.7:1.4-1.5:2.6-2.9.

[0015] In combination with the second aspect, preferably, the amount of pyrrole added is 0.5-2 mL.

[0016] In combination with the second aspect, preferably, the aqueous solution of Co(NO3)2·6H2O, the aqueous solution of 2-methylimidazole and the nickel foam are mixed and reacted for 4-6 hours.

[0017] In combination with the second aspect, preferably, the L-Co-ZIF / NF precursor is dissolved in an aqueous solution of Ni(NO3)2·6H2O and the reaction time is 18-24 hours.

[0018] In combination with the second aspect, preferably, the method of electro-depositing pyrrole onto the surface of the NiCo-LDH / NF includes: using a mixed aqueous solution of pyrrole and p-toluenesulfonic acid as an electrolyte, a saturated calomel electrode as a reference electrode, a platinum sheet electrode as a counter electrode, and NiCo-LDH / NF as a working electrode, and preparing it by CV cycle electrochemical polymerization.

[0019] In combination with the second aspect, preferably, during the CV cycle electrochemical polymerization, the voltage is 0.1-2V and the number of deposition cycles is 1-3.

[0020] The third aspect of the present application provides the use of the PPy / NiCo-LDH / NF composite material prepared by the preparation method described in the second aspect in an electrocatalytic reaction.

[0021] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0022] The PPy / NiCo-LDH / NF composite material provided in the present application is prepared by compounding NiCo layered double hydroxide and polypyrrole on a nickel foam substrate, and polypyrrole is compounded on the surface of the NiCo layered double hydroxide. On the one hand, the surface induction of the NiCo layered double hydroxide by polypyrrole makes the layered double hydroxide arranged more regularly and densely, which is conducive to the efficient mass transfer of electrons and enhances the transfer efficiency between the electrolyte and the active sites; on the other hand, the surface modification of the NiCo layered double hydroxide by polypyrrole can induce the electron transfer interface, so that the composite material exposes more catalytic active sites and enhances the electronic interaction, so that the composite material exhibits excellent electrocatalytic activity in both HER and OER in alkaline media; at the same time, after 1000 cycles, the HER and OER in alkaline media exhibit excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 A process flow chart of the Al-PPy / NiCo-LDH / NF composite material prepared in the examples of the present application;

[0025] Figure 2 Scanning electron microscope images of the NiCo-LDH / NF composite material and the Al-PPy / NiCo-LDH / NF composite material prepared in the examples of the present application;

[0026] Figure 3 This is a SEM-mapping image of the A1-PPy / NiCo-LDH / NF composite material prepared in the example of the present application;

[0027] Figure 4 XRD patterns of the Al-PPy / NiCo-LDH / NF composite material, the NiCo-LDH / NF composite material and the PPy / NF composite material prepared in the examples of the present application;

[0028] Figure 5 HER electrochemical performance diagram of NiCo-LDH / NF composite material, PPy / NF composite material, NF and A1-PPy / NiCo-LDH / NF composite material prepared in the examples of the present application;

[0029] Figure 6 OER electrochemical performance diagram of NiCo-LDH / NF composite material, PPy / NF composite material, NF and A1-PPy / NiCo-LDH / NF composite material prepared in the examples of the present application. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0032] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0033] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0034] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0035] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0036] In a first aspect, an embodiment of the present application provides a PPy / NiCo-LDH / NF composite material, the composite material comprising a nickel foam substrate and a NiCo layered double hydroxide and polypyrrole composited on the nickel foam substrate;

[0037] The polypyrrole is compounded on the surface of the NiCo layered double metal hydroxide.

[0038] Among them, on the one hand, through the surface induction of NiCo layered double hydroxide by polypyrrole, the layered double hydroxide is arranged more regularly and densely, which is conducive to the efficient mass transfer of electrons and enhances the transfer efficiency between the electrolyte and the active sites; on the other hand, through the surface modification of NiCo layered double hydroxide by polypyrrole, the electron transfer interface can be induced, so that the composite material exposes more catalytic active sites and enhances the electronic interaction, so that it exhibits excellent electrocatalytic activity in both HER and OER in alkaline media; at the same time, after 1000 cycles, both HER and OER in alkaline media show excellent cycle stability.

[0039] It should be noted that the NiCo-LDH derived from the L-Co-ZIF material by the ZIF template-guided strategy in this application is arranged in an orderly manner and has a unique morphology, which effectively solves the problem of easy aggregation and poor dispersibility of LDH. The ZIF template has a highly controllable structure and can produce a porous morphology. The central atoms of ZIF are usually metal Ni and Co, making them a material for preparing ordered and unique morphology. By adjusting the ratio of metal Ni, Co ions and organic ligands, the structure and morphology of the ZIF material can be accurately controlled, thereby affecting the arrangement and morphology of the prepared NiCo-LDH. By compounding polypyrrole on the surface of NiCo layered double hydroxide, the polar groups of PPy are combined with active sites such as hydroxyl groups of NiCo-LDH to form more active adsorption sites. At the same time, the conductivity of PPy helps to improve the electronic transport performance of NiCo-LDH, so that it exhibits more excellent conductivity in the electrochemical process, thereby adjusting the ion transfer rate between the electrolyte and NiCo-LDH; and the composite of PPy can also enhance the structural stability of NiCo-LDH, so that it can still maintain good catalytic performance after multiple cycles.

[0040] In a second aspect, the present application also provides a method for preparing the PPy / NiCo-LDH / NF composite material according to the first aspect, the method comprising:

[0041] The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor;

[0042] The L-Co-ZIF / NF precursor is dissolved in an aqueous solution of Ni(NO3)2·6H2O, reacted at room temperature, separated and collected to obtain NiCo-LDH / NF;

[0043] The pyrrole is electrodeposited and polymerized onto the surface of the NiCo-LDH / NF to obtain a PPy / NiCo-LDH / NF composite material.

[0044] It should be noted that this application uses nickel foam (NF) as the substrate material. First, the surface of the nickel foam is pretreated: acetone solution is added to a beaker, the surface of the nickel foam is soaked, and ultrasonic is performed for 20 minutes to remove organic matter on the surface of the nickel foam; then 2mol / L HCl is ultrasonicated for 5 minutes, and finally deionized water is ultrasonicated several times until the pH reaches neutral, and then placed in a 60°C oven for drying for 24 hours for standby use. NF has a high specific surface area, which enables nickel foam to provide a larger reaction area in electrochemical applications, thereby improving the electrocatalytic performance and effectively reducing the energy consumption of the electrochemical reaction. And it is formed by interconnected channels, and the conductive structure inside these channels can improve the transmission of electrons on the substrate, increase its conductivity, and thus improve the efficiency and rate of the electrocatalytic reaction.

[0045] It should be noted that the preparation process of the present application is made through the ZIF template-guided strategy and electrochemical polymerization method. First, the nickel foam is added to the aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole, reacted at room temperature, and the L-Co-ZIF / NF precursor is obtained. Then, the L-Co-ZIF / NF precursor is dissolved in the aqueous solution of Ni(NO3)2·6H2O, reacted at room temperature, separated and collected, and NiCo-LDH / NF is obtained. The NiCo-LDH derived from the L-Co-ZIF material through the ZIF template-guided strategy is orderly arranged and has a unique morphology. Then, pyrrole is electro-deposited and polymerized onto the surface of NiCo-LDH / NF, and the electron transfer interface is induced through surface modification, so that the material exposes more catalytic active sites and enhances the electronic interaction, giving it excellent electrocatalytic activity.

[0046] In the embodiment of the present application, the mass ratio of Co(NO3)2·6H2O, 2-methylimidazole and Ni(NO3)2·6H2O is preferably 0.6-0.7:1.4-1.5:2.6-2.9. Among them, 2-methylimidazole is used as an organic ligand to coordinate with cobalt and nickel ions to form a ZIF structure. By controlling the addition ratio of each substance, the prepared NiCo layered double metal hydroxide can have a nanosheet layered structure and excellent crystallinity.

[0047] In the embodiment of the present application, the amount of pyrrole added is 0.5-2mL. Among them, by controlling the amount of pyrrole added, the amount of polypyrrole introduced into the material is controlled. The amount of pyrrole introduced has a great influence on the performance of the composite material. Too little amount will lead to uneven dispersion of the generated PPy, while too much amount will cause partial agglomeration of NiCo-LDH, affecting the electrocatalytic performance.

[0048] In the embodiment of the present application, the time for mixing the aqueous solution of Co(NO3)2·6H2O, the aqueous solution of 2-methylimidazole and the nickel foam for reaction is preferably 4-6 hours, more preferably 5 hours; the time for dissolving the L-Co-ZIF / NF precursor in the aqueous solution of Ni(NO3)2·6H2O is preferably 18-24 hours, more preferably 24 hours. Among them, a shorter reaction time leads to insufficient crystallinity and uneven particle size distribution, while too long a time induces unnecessary side reactions and affects the purity of the product. Therefore, by controlling each reaction time, a composite material with a nanosheet array structure can be made through a ZIF template-guided strategy.

[0049] In an embodiment of the present application, the method of electro-deposition polymerization of pyrrole onto the surface of the NiCo-LDH / NF includes: using a mixed aqueous solution of pyrrole monomer and p-toluenesulfonic acid as an electrolyte, a saturated calomel electrode as a reference electrode, a platinum sheet electrode as a counter electrode, and NiCo-LDH / NF as a working electrode, and preparing the mixture by CV cycle electrochemical polymerization. During CV cycle electrochemical polymerization, the voltage is preferably 0.1-2V, and the number of deposition cycles is preferably 1-3. Among them, by adopting electrochemical polymerization, polypyrrole is uniformly and stably dispersed onto the surface of the NiCo-LDH / NF composite material. The method has simple equipment, simple operation process, and strong controllability of reaction conditions. It is an environmentally friendly preparation method that can produce a polypyrrole film with uniform thickness, high purity and good reproducibility at room temperature and normal pressure.

[0050] The third aspect of the present application provides the use of the PPy / NiCo-LDH / NF composite material prepared by the preparation method described in the second aspect as a catalyst in an electrocatalytic reaction. Among them, the PPy / NiCo-LDH / NF composite material prepared as above exhibits excellent electrocatalytic activity and structural stability in both HER and OER in alkaline media, and has broad application prospects in electrocatalytic reactions, including electrolytic water hydrogen evolution reaction, electrolytic water oxygen evolution reaction or complete water splitting reaction.

[0051] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0052] Example 1

[0053] This embodiment provides a method for preparing an Al-PPy / NiCo-LDH / NF composite material. Figure 1 The process flow chart shown in the figure is used for preparation, which specifically includes:

[0054] S101: 0.65 g Co(NO3)2·6H2O and 1.46 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained.

[0055] S102: The L-Co-ZIF / NF precursor was immersed and dissolved in a 9.6 mmol Ni(NO3)2·6H2O solution, reacted at room temperature for 24 h, and then cleaned and dried in a vacuum oven at 60°C to obtain NiCo-LDH / NF;

[0056] S103: A three-electrode system was adopted. Pyrrole monomer and p-toluenesulfonic acid aqueous solution were mixed evenly in a ratio of 1:2 and stirred for 20 minutes as the electrolyte. A saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, and NiCo-LDH / NF was used as the working electrode. It was prepared by CV cyclic electrochemical polymerization. The deposition voltage was 0-2V and the number of deposition cycles was 2, thus obtaining the A1-PPy / NiCo-LDH / NF composite material.

[0057] Example 2

[0058] This embodiment provides a method for preparing an A2-PPy / NiCo-LDH / NF composite material, which specifically includes:

[0059] S201: 0.6 g Co(NO3)2·6H2O and 1.5 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained.

[0060] S202: The L-Co-ZIF / NF precursor was immersed and dissolved in a 9.6 mmol Ni(NO3)2·6H2O solution, reacted at room temperature for 24 h, and then cleaned and dried in a vacuum oven at 60°C to obtain NiCo-LDH / NF;

[0061] S203: A three-electrode system was adopted. Pyrrole monomer and p-toluenesulfonic acid aqueous solution were mixed evenly in a ratio of 1:2 and stirred for 20 minutes as the electrolyte. A saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, and NiCo-LDH / NF was used as the working electrode. It was prepared by CV cyclic electrochemical polymerization. The deposition voltage was 0-2V and the number of deposition cycles was 2, thus obtaining the A2-PPy / NiCo-LDH / NF composite material.

[0062] Example 3

[0063] This embodiment provides a method for preparing an A3-PPy / NiCo-LDH / NF composite material, which specifically includes:

[0064] S301: 0.7 g Co(NO3)2·6H2O and 1.4 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained;

[0065] S302: The L-Co-ZIF / NF precursor was immersed and dissolved in a 9.8 mmol Ni(NO3)2·6H2O solution, reacted at room temperature for 24 h, and then cleaned and dried in a vacuum drying oven at 60°C to obtain NiCo-LDH / NF;

[0066] S303: A three-electrode system was used. Pyrrole monomer and p-toluenesulfonic acid aqueous solution were mixed evenly in a ratio of 1:2 and stirred for 20 minutes as the electrolyte. A saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, and NiCo-LDH / NF was used as the working electrode. It was prepared by CV cyclic electrochemical polymerization. The deposition voltage was 0-2V and the number of deposition cycles was 2, thus obtaining the A3-PPy / NiCo-LDH / NF composite material.

[0067] At the same time, in order to verify the comprehensive performance of the PPy / NiCo-LDH / NF composite material prepared in the above embodiment, the present application provides the following comparative examples for detailed description.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a NiCo-LDH / NF composite material, which specifically includes:

[0070] S301: 0.65 g Co(NO3)2·6H2O and 1.46 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained;

[0071] S302: The L-Co-ZIF / NF precursor was immersed and dissolved in a 9.6 mmol Ni(NO3)2·6H2O solution, reacted at room temperature for 24 hours, and then cleaned and dried in a vacuum drying oven at 60°C to obtain a NiCo-LDH / NF composite material.

[0072] Comparative Example 2

[0073] This comparative example provides a method for preparing a PPy / NF composite material, which specifically includes:

[0074] S401: A three-electrode system was used. Pyrrole monomer and p-toluenesulfonic acid aqueous solution were mixed evenly in a ratio of 1:2 and stirred for 20 minutes as the electrolyte. A saturated calomel electrode was used as the reference electrode, a platinum electrode was used as the counter electrode, and NF was used as the working electrode. It was prepared by CV cyclic electrochemical polymerization. The deposition voltage was 0-2V and the number of deposition cycles was 2, thus obtaining a PPy / NF composite material.

[0075] Comparative Example 3

[0076] The material provided in the comparative example of the present application is subjected to comparative testing using pure nickel foam without compounding NiCo layered double hydroxide and polypyrrole, which is recorded as NF.

[0077] In order to verify the morphology and structure of the PPy / NiCo-LDH / NF composite material prepared in the example of the present application, the structural performance of the PPy / NiCo-LDH / NF composite material prepared in the example was characterized, and the results were as follows: Figure 2-Figure 4 As shown; among them, Figure 2 Scanning electron microscopy images of NiCo-LDH / NF composites and A1-PPy / NiCo-LDH / NF composites; Figure 3 SEM-mapping image of A1-PPy / NiCo-LDH / NF composite material; Figure 4 XRD patterns of A1-PPy / NiCo-LDH / NF composite material, NiCo-LDH / NF composite material and PPy / NF composite material.

[0078] according to Figure 2 As we know, these are scanning electron microscope images of A1-PPy / NiCo-LDH / NF composite materials and NiCo-LDH / NF composite materials, where a) is NiCo-LDH / NF composite materials and b) is A1-PPy / NiCo-LDH / NF composite materials. From Figure a), we can see that the overall arrangement of NiCo-LDH / NF composite materials is a layered nanosheet layer, which is arranged more regularly after the template, and this arrangement is conducive to high-quality transmission of electrons. From Figure b), we can see that PPy makes the distribution of NiCo-LDH nanostructured sheets more dense and the surface rougher, which is conducive to efficient mass transfer of electrons, enhances the transfer efficiency between electrolytes and active sites, and is conducive to improving electrocatalytic performance.

[0079] according to Figure 3As known, this is the SEM-mapping image of A1-PPy / NiCo-LDH / NF composite material. The PPy / NiCo-LDH / NF composite material is composed of Ni, Co, C, O and N elements, and is evenly distributed on the surface of the composite material, indicating that PPy is successfully polymerized on the NiCo-LDH surface.

[0080] according to Figure 4 As we know, the diffraction peak of pure PPy appears very broad at 20°-30°, proving that it is an amorphous structure of C in PPy. The three characteristic peaks at 44.5°, 51.8° and 76.3° in the XRD patterns of NiCo-LDH / NF and PPy / NiCo-LDH / NF composites are respectively attributed to the (111), (200) and (220) crystal planes of elemental Ni (JCPDS: No.04-0850). In addition to the characteristic diffraction peaks of the foamed nickel substrate, the five characteristic diffraction peaks at 2θ=11.6°, 23.1°, 34.9°, 37.7° and 60.6° correspond to the (003), (006), (012), (104) and (110) crystal planes of NiCo-LDH (JCPDS: No.40-0216), indicating that the NiCo-LDH / NF composite was successfully prepared. In addition, the diffraction peak intensity of PPy in the PPy / NiCo-LDH / NF composite is very high, indicating that the crystal form is complete.

[0081] In order to verify the performance of the PPy / NiCo-LDH / NF composite material prepared in the examples of the present application as a catalyst in the HER and OER electrochemistry of water electrolysis, the HER and OER electrocatalytic activity tests were carried out on the PPy / NiCo-LDH / NF composite material prepared in the examples.

[0082] The Hg / HgO electrode was used as the reference electrode, the graphite rod was used as the counter electrode, and the catalyst prepared in Example 1 was used as the working electrode. Potential reference reversible hydrogen electrode (RHE): E RHE =E Hg / HgO + 0.098 + 0.059 × pH (1M KOH solution). Calculate the overpotential (η): η = E RHE -1.23 V. All electrode potential data were 90% iR compensated.

[0083] In the electrochemical performance test, the three-electrode system was used to test the OER and HER electrocatalytic performance on an electrochemical workstation (CHI760E). When testing, the working electrode was first activated by cyclic voltammetry (CV) at a scan rate of 10mV / s until the CV curves were highly overlapped, the oxygen evolution reaction voltage range was 0 to 1V (vs. RHE), and the hydrogen evolution reaction voltage range was -0.9 to -1.4V (vs. RHE).

[0084] according to Figure 5 As we know, Figure 5 As shown in (a), when the current density reaches 10 mA / cm 2 The overpotential is only 133 mV, which is lower than the overpotentials of PPy (224 mV), NiCo-LDH / NF (237 mV) and NF (283 mV), proving that the in-situ polymerization of PPy successfully and effectively improves the HER performance. The Tafel slope reveals the intrinsic reaction kinetics of HER. Figure 5 As shown in (b), the Tafel slope value of PPy / NiCo-LDH / NF (63.2 mV / dec) is smaller than that of PPy (90.9 mV / dec), NiCo-LDH / NF (120 mV / dec) and NF (265.2 mV / dec). This shows that the HER catalytic process of PPy / NiCo-LDH / NF follows the Volmer-Heyrovsky reaction mechanism, and its rate-limiting step is the electrochemical desorption process. For the practical application of the catalyst, it is necessary not only to have excellent performance but also excellent stability. The IT curve for testing stability is shown in Figure 5 As shown in (c), the stability of the PPy / NiCo-LDH / NF composite material was maintained for about 24 h at a constant voltage of -1.06 V, and the current density retention rate was 96.2%. Figure 5 (d) is the cycling performance test of PPy / NiCo-LDH / NF, comparing the change in overpotential of the material in the initial state and after 1000 CV cycles by linear sweep voltammetry. 2 The overpotential at the current density increased by 4 mV, indicating that PPy / NiCo-LDH / NF has good cycling stability as a HER catalyst.

[0085] according to Figure 6 As far as we know, the PPy / NiCo-LDH / NF composite material has a 2 The overpotential at 10 mV / cm2 is 235 mV, showing good OER catalytic activity. However, the overpotentials of NiCo-LDH / NF, PPy, and NF are higher, requiring overpotentials of 270, 379, and 399 mV, respectively, to reach 10 mV / cm2. 2 Current density ( Figure 6 (a)). In addition, Figure 6(b) shows the Tafel slopes of the above catalysts. The Tafel slope of the PPy / NiCo-LDH / NF composite material is 74.5 mV / dec, which is smaller than the Tafel slopes of the NiCo-LDH / NF (109.2 mV / dec), PPy / NF (233.7 mV / dec), and NF (282.8 mV / dec) catalysts. The results show that the kinetic performance of the PPy / NiCo-LDH / NF composite material is the best. The stability of the material was tested by chronoamperometry. Figure 6 (c) is the chronoamperometric test of PPy / NiCo-LDH / NF. After 24 hours of continuous current testing, the current density did not show a significant decrease. Figure 6 As shown in (d), after 1000 CV cycles, the LSV curve of the PPy / NiCo-LDH / NF composite material almost coincides with the initial LSV curve of the reaction, which indicates that its activity has not been significantly attenuated after 1000 CV cycles, and the OER capacitance retention rate is 96.7%, further confirming that the PPy / NiCo-LDH / NF composite material has good catalytic stability in OER in alkaline electrolyte.

[0086] Therefore, the present invention successfully synthesized PPy / NiCo-LDH / NF nanosheet arrays through the ZIF template-guided strategy and electrochemical polymerization method, which showed excellent electrocatalytic activity for both HER and OER in alkaline media with a current density of 10 mA / cm 2 When PPy is used, the overpotentials are 133mV and 235mV, respectively. The surface modification of NiCo-LDH by PPy induces an electron transfer interface, which exposes more catalytic active sites on the composite material and enhances the electronic interaction, greatly promoting the decomposition of water, and has broad application prospects in electrocatalytic reactions.

[0087] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0088] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A PPy / NiCo-LDH / NF composite material, characterized in that: The composite material comprises a nickel foam substrate and NiCo layered double metal hydroxide and polypyrrole composited on the nickel foam substrate; The polypyrrole is compounded on the surface of the NiCo layered double metal hydroxide.

2. The PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that The composite material has a nanosheet array structure.

3. A method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The method comprises: The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor; The L-Co-ZIF / NF precursor is dissolved in an aqueous solution of Ni(NO3)2·6H2O, reacted at room temperature, separated and collected to obtain NiCo-LDH / NF; The pyrrole is electrodeposited and polymerized onto the surface of the NiCo-LDH / NF to obtain a PPy / NiCo-LDH / NF composite material.

4. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The mass ratio of Co(NO3)2·6H2O, 2-methylimidazole and Ni(NO3)2·6H2O is 0.6-0.7:1.4-1.5:2.6-2.

9.

5. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The amount of pyrrole added is 0.5-2 mL.

6. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The aqueous solution of Co(NO3)2·6H2O, the aqueous solution of 2-methylimidazole and the nickel foam are mixed and reacted for 4-6 hours.

7. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The L-Co-ZIF / NF precursor is dissolved in an aqueous solution of Ni(NO3)2·6H2O and the reaction time is 18-24 hours.

8. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 1, characterized in that: The method of electro-depositing pyrrole onto the surface of the NiCo-LDH / NF comprises: using a mixed aqueous solution of pyrrole monomer and p-toluenesulfonic acid as an electrolyte, a saturated calomel electrode as a reference electrode, a platinum sheet electrode as a counter electrode, and NiCo-LDH / NF as a working electrode, and preparing the product by CV cycle electrochemical polymerization.

9. The method for preparing the PPy / NiCo-LDH / NF composite material according to claim 8, characterized in that: During the CV cycle electrochemical polymerization, the voltage is 0.1-2V and the number of deposition cycles is 1-3.

10. Use of the PPy / NiCo-LDH / NF composite material prepared by the preparation method according to any one of claims 3 to 9 in an electrocatalytic reaction.

Citation Information

Patent Citations

  • Preparation method and application of nickel-cobalt layered hydroxide coated polypyrrole tube composite material

    CN116825548A

Cited By

  • Catalytic anode with conductive polymer intercalation and preparation method and application thereof

    CN120026366A

  • Wheat-ear-shaped super-hydrophilic-super-aerophobic cobalt-iron-based electrocatalyst and application thereof

    CN121915452A

  • Three-dimensional multilayer LDH / CS / PPy composite material and preparation method and application thereof

    CN121983433A